A novel proposal to effectively combine multipath data forwarding for data center networks with congestion control and load balancing using Software-Defined Networking Approach - Mallik, Arijit; Hegde, Saumya (2014 International Conference on Recent Trends in Information Technology, 2014)
Modern data center networks (DCNs) often use multi-rooted topologies, which offer multipath capability, for increased bandwidth and fault tolerance. However, traditional routing algorithms for the Internet have no or limited support for multipath routing, and cannot fully utilize available bandwidth in such DCNs. As a result, they route all the traffic through a single path, and thus form congestion. Multipath (MP) routing might be a good alternative, but is not sufficient alone to handle congestion that comes from the contention of end stations. Dynamic load balancing, on the other hand, protects the network from sudden congestions which could be caused by load spikes or link failures. However, little work has been done to incorporate all these features in a single and comprehensive solution for Data Center Ethernet (DCE). In this paper, we propose a novel method that attempts to integrate dynamic load balancing, multi-path scheme with congestion control (CC), with the use of pure Software-Defined-Networking (SDN) approach. SDN decouples control plane from the data forwarding plane, which reduces the overheads of the network switches. The major objectives that our solution attempts to achieve are, efficient utilization of network resources, high throughput and minimal frame loss.